Farmers' Risk Perception, Risk Aversion on Manggosteen Production (Case Study in Pauh Thematic Village) - Cindy Paloma; Rika Hariance; Syahyana Raesi; Afrianingsih Putri (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2024)
The mangosteen commodity has become a leading product of West Sumatra Province due to its large export market share, which requires farmers to maintain the quantity and quality of the mangosteen they produce. Mangosteen has a high economic value, but its cultivation is still traditional, and the quality produced is not entirely in line with the expectations of the export destination countries. Since 2021, the Mayor of Padang has designated the Pauh District as a thematic mangosteen village, but fluctuations in mangosteen production indicate risks. This research analyzes the relationship between farmer characteristics and their attitude toward mangosteen production risks. The research method involves a survey and the sampling of 40 farmers using purposive sampling. Data was collected from June to July 2023. The level of risk is analyzed using the coefficient of variation method, while farmer risk behavior is assessed using the Moscardi and de Janvry method. Factors influencing farmers are analyzed using Ordinary Least Square (OLS) regression. The research results indicate a production risk for mangosteen with a coefficient of variation value of 0.47 (47%). Most farmers, 38 out of 40 (98%), exhibit a risk-averse behavior, while two farmers (2%) have a neutral risk attitude. The characteristics of farmers that significantly influence their risk behavior are age, farming experience, and farming income.